European Community and US-FDA Approval of Recombinant Human Antithrombin Produced in Genetically Altered Goats - (:unkn) unknown (SAGE PUBLICATIONS INC, 2009)
Thrombin and factor Xa play a central role in thrombogenesis in both medical and surgical patients. Antithrombin (AT) is the key inhibitor, which controls the action of these enzymes in hypercoagulable states. The AT concentrates prepared from human blood have been used to treat patients with thrombotic disorders and heparin resistance. The AT concentrates are prepared from pooled human plasma and beside limited supply, suffer from viral and other biological contaminants. The availability of recombinant human AT (rhAT) obtained from genetically engineered goats provide a biologically equivalent product that can be used in practically all indications where human AT is indicated including heparin resistance. Moreover, because of its high affinity to heparin and related drugs, recombinant AT can also be developed in further indications. On review of the preclinical and clinical data on the safety and efficacy, the European Union and U.S. Food and Drug Administration (US-FDA) have recently approved the use of rhAT in specified clinical indications.
Keywords: recombinant antithrombin; hypercoagulability; thrombosis; genetically altered goats; antithrombin deficiency; ANTI-THROMBIN-III; HEPARIN-RESISTANT PATIENTS; MAMMARY-GLAND; CARDIOPULMONARY BYPASS; DEFICIENCY STATES; TRANSGENIC GOATS; MILK; EXPRESSION; HETEROGENEITY; COAGULATION